KHAZANAH ARSIP SEBAGAI KOLEKSI MUSEUM: STUDI KASUS ARSIP MAKAM BELANDA PENELEH DI MUSEUM SIOLA SURABAYA: Array - Syah Irza Raya; Tamara Adriani Salim (Arsip Nasional Republik Indonesia, 2019)
Museum Siola Surabaya has been keeping both artefact and paper-based colonial archives since 2015. What matters the most are to provide various sources of history of Surabaya, such as old furnitures, Surabaya topography maps, pictures of Surabaya mayors, city’s placard and certificate and Peneleh Dutch Cemetery archives. Before 2015, the archives were kept by Hygiene and Green Public Outdoor Service that has authority to manage cemetery at Surabaya. Unfortunately there are only limited pages of archives that are safe to be exhibited, such as cemetery map, the deceased biographies and cemetery register books. The archives kept as one